2017
DOI: 10.1073/pnas.1703100114
|View full text |Cite
|
Sign up to set email alerts
|

Treg-specific IL-27Rα deletion uncovers a key role for IL-27 in Treg function to control autoimmunity

Abstract: Dysregulated Foxp3 Treg functions result in uncontrolled immune activation and autoimmunity. Therefore, identifying cellular factors modulating Treg functions is an area of great importance. Here, using Treg-specific mice, we report that IL-27 signaling in Foxp3 Tregs is essential for Tregs to control autoimmune inflammation in the central nervous system (CNS). Following experimental autoimmune encephalomyelitis (EAE) induction, Treg-specific mice develop more severe EAE. Consistent with the severe disease, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 35 publications
5
77
0
Order By: Relevance
“…Intranasal IL-27 administration fails to inhibit airway inflammation without Foxp3 + Tregs, and adoptive Foxp3 + Treg transfer restores the inhibition. We recently reported that Foxp3 + Tregs control the development of allergic airway inflammation and that IL-27 signaling in Foxp3 + Tregs is essential to control Th17-mediated autoimmune inflammation (19,20). Whether Tregs are essential during IL-27-mediated inhibition of allergic airway inflammation was next examined using Foxp3 DTR mice (23).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Intranasal IL-27 administration fails to inhibit airway inflammation without Foxp3 + Tregs, and adoptive Foxp3 + Treg transfer restores the inhibition. We recently reported that Foxp3 + Tregs control the development of allergic airway inflammation and that IL-27 signaling in Foxp3 + Tregs is essential to control Th17-mediated autoimmune inflammation (19,20). Whether Tregs are essential during IL-27-mediated inhibition of allergic airway inflammation was next examined using Foxp3 DTR mice (23).…”
Section: Resultsmentioning
confidence: 99%
“…Allergen-induced allergic airway inflammation is exacerbated in Treg-specific Il27ra -/mice. To precisely determine the role of IL-27 signaling in Treg functions during allergic airway infiltration, Treg-specific Il27ra -/mice (Treg ΔIl27ra ) were next used (19). Treg ΔIl27ra and littermate Treg WT control mice were induced for allergic airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations